PEMBUATANCHEWYCHOCOCORNCOOKIESDENGANSUBSTITUSITEPUNG JAGUNGSEBAGAIPRODUKCOOKIESKAYASERAT - Marwanti, ArifiaAlfyFachriz (Prosiding Pendidikan Teknik Boga Busana, 2020)
Thisresearchisintendedtoincreaseconsumptionoflocalfoodproductsthroughdevelopment productsthatarealreadyonthemarketandareindemandbythepublic.Thetypeofresearchusedis ResearchandDevelopmentwiththe4Ddevelopmentmodel(Define,Design,Develop,Disseminate).The placeandtimeofthestudywereconductedattheCateringLaboratory,thePTBBDepartmentofthe FacultyofEngineering,YogyakartaStateUniversity,wasconductedfromJanuarytoApril2019.The testmaterialwasasampleofeachproduct. Thetestingtoolsusedwereexperimentalforms, validationforms,panelistsensorytestformsandfavoritetestforms.Intheprocessofprocessing cookiesnoglutenisneeded,sothatthedoughprocessistriednottoolongbecauseifittakestoolong itwillcauseglutenformationandwillcausecookiestobecomehard.Theresultsofthisstudyindicate that:a)thestandardrecipeforchewychococorncookieswithsubstitutionof60%cornflour,b) communityacceptanceofchewychococorncookies3.8,whichmeansitisverypopular,c)fiber contentinchewychococorncookiesamountingto59.04gr